(untitled) (Contemporary Central & East European Law, 2024)
The course of administrative proceedings is documented in the files of an administrative case. Over the development of administrative law, the legislator has established various legal regimes to guarantee that entitled persons have access to all or part of the procedural materials collected in these case files. This article aims to present the two basic regimes of access to case files and analyze their interrelationship. The research demonstrates that, although the regulatory scope of these regimes partially overlaps, there are significant differences in terms of their subject and object. Nevertheless, mutual interaction between these regimes is evident, particularly in how they have evolved over time. The paper concludes with a negative answer to the question of whether the right to public information can substitute a party’s information rights under the Administrative Procedure Code. Each of the two access regimes serves a distinct purpose and is governed by specific regulations tailored to that purpose.